A Review on Kushthaghna Mahakashaya - Agrawal, Aaditi; Kushwaha, Ashwini Kumar (International Research Journal of Ayurveda & Yoga, 2022)
The broad term used in Ayurveda for all types of skin disorders is Kushtha, depending on the severity of the disease Kushtha is further classified as Mahakushtha and Kshudrakushtha. According to the Acharyas, Kushtha arises due to the vitiation of seven factors, of which three are doshas (Vata, Pitta and Kapha) and four are Dushyas (Tvaka, Mamasa, Shonita and laseeka). Acharyas have classified eighteen types of Kushtha on the basis of the predominance of seven factors, out of which seven are Mahakushtha and eleven are Kushdrakushtha. The Ayurvedic classics attach great importance to Kushtha which is evident from the fact that the treatment of Kushtha is described in the third chapter of Charaka Samhita where external therapeutics for the disease are explained. In the fourth chapter of Sutrasthan of Charaka Samhita, Acharya Charaka has described a group of ten medicines for skin diseases under Kushthaghna mahakashaya. Most skin diseases have a close link to psychological stress, and stress is responsible for the onset and worsening of several skin problems. Rasayan (rejuvenation) qualities were recorded in the majority of the medications in the Kushthaghna Mahakashyaya. As a result, these medications aid in lowering the adverse effects of stress and thus aid in the management of chronic skin problems. In this paper drugs of Kushthaghna mahakashaya has been reviewed on scientific lines through published work and it is observed that the drugs have various related activity.